Percepción de la población sobre el servicio de agua potable en dos asentamientos humanos del distrito de Punchana-provincia de Maynas 2021 - Java Barboza, Frank Michel (2023)
The objective of this research work was to study the perceptions of the population about the drinking water service in two AAHH of the Punchana district of the province of Maynas in 2021. The research, due to its approach, was quantitative, prospective, descriptive level simple and non-experimental research design. The target population of the study consisted of (450 dwellings or heads of families) with a minimum of two years of experience and with housing in the place. The sample also consisted of 65 heads of families distributed in 34 heads of families of AAHH Versalles and 31 heads of families of AAHH Masusa, who were present at the time of application of the data collection instrument, criteria were taken into account. of inclusion and exclusion, the technique that was used was the survey and the measurement instrument applied was the questionnaire of thirteen questions, the same one that passed the tests of validity (Aiken's validity index) and reliability (test of the two halves). The data obtained through the data collection instrument was analyzed taking into account the objectives and the research hypothesis and later expressed in a Basic Data Matrix (MBD) and analyzed and tabulated through the statistical package SPSS version 23. The main The results expressed that, regarding the service in the homes and storage of drinking water in both AAHH, this is done mostly of the public service and stores it in buckets or drums (52.9%) and (71%), the scarcity of water is the main problem (55.9% and 51.2%) since its frequency is mostly every three days (55.9% and 77.4 %), the type of water for consumption by the population in both AAHH is preferably boiled (50% and 58.1%), the quality of water consumed by the population was mostly of poor quality (61.8% and 71%), monthly water consumption in both varies from 40 to 60 soles mostly (50% and 51.6%), there is presence of diseases in all family members and in children under 12 years (52.9% and 58.1%) and 79.4% and 77.4% of the residents of both AAHH said they agreed with the installation of drinking water meters. The research hypothesis assumed in this investigation does not agree with the results obtained in this work.